Global Change Can Make Coastal Eutrophication Control in China More Difficult. Issue 4 (29th March 2020) - Wang, Mengru; Kroeze, Carolien; Strokal, Maryna; van Vliet, Michelle T. H.; Ma, Lin
Abstract: Fast socio‐economic development in agriculture and urbanization resulted in increasing nutrient export by rivers, causing coastal eutrophication in China. In addition, climate change may affect hydrology, and as a result, nutrient flows from land to sea. This study aims at a better understanding of how future socio‐economic and climatic changes may affect coastal eutrophication in China. We modeled river export of total dissolved nitrogen (TDN) and phosphorus (TDP) in 2050 for six scenarios combining socio‐economic pathways (SSPs) and Representative Concentration Pathways (RCPs). We used the newly developed MARINA 2.0 (Model to Assess River Inputs of Nutrients to seAs) model. We found that global change can make coastal eutrophication control in China more difficult. In 2050 coastal waters may be considerably more polluted or considerably cleaner than today depending on the SSP‐RCP scenarios. By 2050, river export of TDN and TDP is 52% and 56% higher than in 2012, respectively, in SSP3‐RCP8.5 (assuming large challenges for sustainable socio‐economic development, and severe climate change). In contrast, river export of nutrients could be 56% (TDN) and 85% (TDP) lower in 2050 than in 2012 in SSP1‐RCP2.6 (assuming sustainable socio‐economic development, and low climate change). Climate change alone may increase river export of nutrients considerably through hydrology: We calculate 24% higher river export of TDN and 16% higher TDP for the SSP2 scenario assuming severe climate change compared to the same scenario with low climate change (SSP2‐RCP8.5 vs. SSP2‐RCP2.6). Policies and relevant technologies combining improved nutrient management and climate mitigation may help to improve water quality in rivers and coastal waters of China. Plain Language Summary: Fast socio‐economic development has resulted in increasing nutrient export by rivers, causing coastal eutrophication in China. In addition, climate change may affect river discharge, and as a result, nutrient flows from land to sea. We explored how future socio‐economic and climatic changes may affect coastal eutrophication in China. We found that in 2050 coastal waters may be considerably more polluted or considerably cleaner than today depending on the socio‐economic development and climate change. By 2050, river export of total dissolved nitrogen (TDN) and phosphorus (TDP) is 52% and 56% higher than in 2012, respectively, in a scenario assuming large challenges for sustainable socio‐economic development and severe climate change. In contrast, river export of nutrients could be 56% (TDN) and 85% (TDP) lower in 2050 than in 2012 in the scenario assuming sustainable socio‐economic development and low climate change. Climate change alone may increase river export of nutrients considerably: we calculate 24% higher river export of TDN and 16% higher TDP for a scenario assuming severe climate change compared to the same scenario with low climate change. Policies combining improved nutrient management and climate mitigation may help to improve water quality in rivers and coastal waters of China. Key Points: In 2050, rivers in China may be more polluted or cleaner, depending on socio‐economic and climatic changes Climate change may increase nutrient pollution in rivers and coastal eutrophication in China Coastal eutrophication can be reduced by nutrient management and climate mitigation